Programming Smalltalk – Object-Orientation from the Beginning An introduction to the principles of programming - Brauer, Johannes (Springer, 2015)
Smalltalk is an outstanding technology. It has been in the forefront of many innovations that have helped to advance the art of application software development such as GUIs with overlapping windows, the mouse, handheld devices, web applications, object-oriented programming, test-driven development and extreme programming, just to name a few. Smalltalk was at the core of a revolution to enable true personal computing. This revolu tion would eventually lead to the creation of a generic device that would allow people to help solve their problems back in the late 1960s and 1970s, an era that knew only large centralised data centres...